1962
DOI: 10.1126/science.135.3506.787
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activity of Plasma and Serum

Abstract: Human plasma and serum were obtained from blood of resting persons. Plasminogen was determined by activation with the optimal amount of streptokinase. As in the majority of cases no significant difference was found between the proteolytic activity of plasma and serum, a blood clot cannot contain more plasminogen than that present in the volume of serum included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

1962
1962
1984
1984

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 5 publications
2
5
1
Order By: Relevance
“…We have confirmed that plasma and serum do not differ significantly in their plasminogen content (3,4). In addition we have found that the formation of an in vitro thrombus is not associated with loss of plasminogen from the blood from which it is made, and direct measurement of the plasminogen content of thrombi suggests that serum trapped in its interstices may account for the small amount of plasminogen found.…”
Section: Discussionsupporting
confidence: 73%
“…We have confirmed that plasma and serum do not differ significantly in their plasminogen content (3,4). In addition we have found that the formation of an in vitro thrombus is not associated with loss of plasminogen from the blood from which it is made, and direct measurement of the plasminogen content of thrombi suggests that serum trapped in its interstices may account for the small amount of plasminogen found.…”
Section: Discussionsupporting
confidence: 73%
“…This was different from the observation of Fantl [12] who found the same activity both in plasma and in serum. However, he had added the equi valent amounts of sodium citrate that was present in the plasma to the serum before the measurement, while we did not.…”
Section: Resultscontrasting
confidence: 52%
“…If this supposition were correct a marked difference between the plasminogen content of plasma and serum would be expected. It has been demonstrated, however, that such a difference does not or hardly exist [7].…”
Section: Discussionmentioning
confidence: 99%